Eco-friendly porous concrete using bottom ash aggregate for marine ranch application. Issue 3 (March 2016) - Lee, Byung Jae; Prabhu, G Ganesh; Lee, Bong Chun; Kim, Yun Yong
This article presents the test results of an investigation carried out on the reuse of coal bottom ash aggregate as a substitute material for coarse aggregate in porous concrete production for marine ranch applications. The experimental parameters were the rate of bottom ash aggregate substitution (30%, 50% and 100%) and the target void ratio (15%, 20% and 25%). The cement-coated granular fertiliser was substituted into a bottom ash aggregate concrete mixture to improve marine ranch applications. The results of leaching tests revealed that the bottom ash aggregate has only a negligible amount of the ten deleterious substances specified in the Ministry of Environment – Enforcement Regulation of the Waste Management Act of Republic Korea. The large amount of bubbles/air gaps in the bottom ash aggregate increased the voids of the concrete mixtures in all target void ratios, and decreased the compressive strength of the porous concrete mixture; however, the mixture substituted with 30% and 10% of bottom ash aggregate and granular fertiliser, respectively, showed an equal strength to the control mixture. The sea water resistibility of the bottom ash aggregate substituted mixture was relatively equal to that of the control mixture, and also showed a great deal of improvement in the degree of marine organism adhesion compared with the control mixture. No fatality of fish was observed in the fish toxicity test, which suggested that bottom ash aggregate was a harmless material and that the combination of bottom ash aggregate and granular fertiliser with substitution rates of 30% and 10%, respectively, can be effectively used in porous concrete production for marine ranch application.